ADAPTING I-PASS HANDOFF PROGRAM FOR EFFECTIVE COMMUNICATION NURSING HANDOFF: A SYSTEMATIC REVIEW - Nur, Rezeki; K, Dewi Hestiani (Media Inovasi Pendidikan dan Publikasi, 2023)
The Join Commission's evaluation showed that more than 3800 patients were harmed and 65% of these were due to communication errors and half of these took place during the handoff process, with recent estimates suggesting that 80% of serious errors in patient care are due to errors during handoff. Poor communication and information obtained during ineffective and non-standardised handoffs can jeopardise patient safety. This study aims to identify the implementation of the I-PASS verbal handoff bundle. The method used is systematic review is made based on the results of the collection of scientific research in the range of 2011-2019 obtained from pubmed, sciencedirect, willey online, proquest and ebsco. There are 3 prospective cohort studies, 2 quasi-experiment studies and 1 mixed methods. Results showed that the I-PASS handoff bundle had an effect on improving communication during the handoff process. It was concluded that I-PASS is one option that can be used in the context of hospital care and nursing curricula and showed that there was a decrease in hospital errors related to communication errors during the handoff process.